Anti-insulin resistant effect of ferulic acid on high fat diet-induced obese mice - Jarinyaporn Naowaboot; Pritsana Piyabhan; Pholawat Tingpej; Narongsuk Munkong; Wason Parklak; Patchareewan Pannangpetch (Asian Pacific Journal of Tropical Biomedicine, 2018)
Objective: To evaluate the insulin sensitivity action of ferulic acid (FA) in skeletal muscle and hypothalamus of high-fat diet (HFD)-induced obese mice. Methods: Obese mouse model was induced by HFD (45 kcal% lard fat) for 16 weeks. After 8 weeks of HFD feeding, these obese mice were orally treated with FA at doses of 25 and 50 mg/kg/day for 8 weeks. At the end of all treatments, the epididymal fat, pancreas, skeletal muscle and hypothalamus were removed for biochemical parameter and protein expression examinations. Results: FA treatment significantly decreased leptin level in fat tissue and insulin level in pancreas (P < 0.05). Interestingly, obese mice treated with FA increased the protein expressions of insulin receptor substrate-1, phosphatidylinositol 3-kinase, and phosphorylated-protein kinase B in both muscle and brain (P < 0.05). The phosphorylations of adenosine monophosphate-activated protein kinase and acetyl-CoA carboxylase in muscle, and leptin receptor protein in hypothalamus were also increased (P < 0.05). The pancreatic islets histology showed smaller size in obese mice treated with FA compared to untreated obese mice. Conclusions: These findings indicate the beneficial effect of FA in improving insulin resistance in HFD-induced obese mice. These effects are probably mediated via modulating the insulin receptor substrate/phosphatidylinositol 3-kinase/protein kinase B or adenosine monophosphate-activated protein kinase pathways.